Comparison of high-density and low-density neoprene knee sleeves on back squat and CMJ performance - Jorge Leschot Gatica; Eduardo Guzman Muñoz; Miguel Alarcón-Rivera; Marco Montoya-Ramos Montoya Ramos; Lytton Leiva-Díaz (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Neoprene knee sleeves are widely used as ergogenic aids in strength sports to enhance performance and reduce injury risk. High-density (HD) models have recently emerged, offering greater stiffness and support compared to traditional low-density (LD) sleeves.